ANTI-CRISIS STRATEGY OF THE TRANSPORT ORGANIZATION - M. Maltseva (Publishing House of the State University of Management, 2018)
The article considers the role of the anti-crisis strategy in the management system of the transport organization. The essence, the goals of the task of anti-crisis management are discussed. Methodological approaches to formation of the model of anti-crisis management of transport enterprises as part of their financial and production activities are proposed. The specifics of the management of the transport organization in conditions of uncertainty and risk are identified, and the main reasons for the insolvency of transport companies are considered. The factors influencing the formation of the anti-crisis strategy are traced, the importance of evaluating the long-term prospects of the enterprise development, analyzing its capabilities, as well as the influence of external factors, is emphasized. The stages of improving the management system of the transport organization are outlined.